3RD APUCEN SUMMIT TO STRENGTHEN NETWORK BETWEEN MEMBERS WORLDWIDE - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 8 March 2017 The 3rd AsiaPacific UniversityCommunity Engagement Network (APUCEN) Summit will bring together close to 87 members from all over the world to Penang on the 3 – 4 April 2017 at Jen Hotel Penang.